Comparison of Laparocopic Appendisectomy (LA) Versus Open Appendisectomy (OA) (A Prospective Randomizing Audit of 1000 Cases) (Medical Forum Monthly, 2024)
Objective: In this Study Comparison between Laproscopic & Open Appendisetomy with regard the length of operation, complication, conversion rate, postoperative hospital stay and time of return to normal activity has been made in order to assess the benefits and feasibility of the procedures.Study Design: Prospective Randomizing study.Place and Duration of study: This study is carried out at Shaheed Mohtrama Benazir Bhutto Medical University (SMBBMU) Hospital and at Sachal Medical Centre Larkana with effect from Jan: 2002 to Jan: 2011.Patients and Methods: All patients with diagnosis of acute appendicitis were enlisted and randomized to either laparoscopic appendisectomy (LA) or Open appendisectomy (OA). All patient received pre-operative antibiotic. The operative time was calculated beginning with incision or insertion of Trocar till the wound was fully closed. Patients those were converted from LA to OA were considered separately. Assessment regarding the return to normal activity and work determined by questioning during the postoperative follow-up.Results: This randomized study of 1000 cases in which 450 cases underwent OA and 550 patients scheduled for the LA procedure but successfully performed 505 and remaining 55 underwent Lap-Converted open appendisectomy. From this study reveals that the common presentation of appendicitis is simple appendicitis next is perforated appendicitis, while the reasons for lap converted open cases were of appendicular mass, perforated appendicitis, gangrenous appendicitis but 2 cases were noted of having normal appendix with pelvic inflammatory disease (PID). The conversion rate remains higher in our study. Operative time in OA/LA remain 81/40minutes. Wound infection rate in OA/LA remain 5.4%/3.0% Hospital stay in OA/LA 5-6/1-2days. Patient return to normal activity in OA/LA group 14days/7days. However early return to job found in LA than OA group of patients.Conclusion: After the long assessment of this study also compared with world literature that the LA is superior because of less pain, minimum wound infection, less operative time. Having the, cosmetically acceptable small scar, less hospital stay & early return to normal activity and job. Therefore this is mature time to say that LA is superior procedure in our setup while can replace open appendisectomy (OA).